Jews, Christians, and Muslims in medieval and early modern times : a festschrift in honor of Mark R. Cohen - Cohen, Mark R., 1943-; Franklin, Arnold E. 1971- (Christians and Jews in Muslim Societies, 2014)
This volume brings together articles on the cultural, religious, social and commercial interactions among Jews, Christians and Muslims in the medieval and early modern periods. Written by leading scholars in Jewish studies, Islamic studies, medieval history and social and economic history, the contributions to this volume reflect the profound influence on these fields of the volume's honoree, Professor Mark R. Cohen.